A Review paper on Business Intelligence - Partap Singh Chauhan, Abhay; Mehta, Saksham; Sharma, Sneha (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 10 No 1&2 (2023): Journal of Advanced Research in Instrumentation and Control Engineering, 2023)
This review paper provides a comprehensive overview of the concept of business intelligence (BI) and its significance in modern organizations. It begins with a brief history of BI, followed by a discussion of its fundamental principles, components, technologies. The paper then highlights the benefits of BI in decision-making, performance monitoring, strategic planning. Additionally, it examines the challenges faced in BI implementation, including data quality issues, organizational culture, technical limitations. The review concludes by identifying the emerging trends and future directions in BI, such as big data analytics, artificial intelligence, cloud computing, their potential impact on the field. Overall, this paper aims to provide a valuable resource for researchers, practitioners, students interested in understanding the role and importance of BI in today’s business environment